Strategi Pembelajaran Berbasis Problem Based Learning (PBL) pada Jamaah Umroh PT Annisa Ahmada Travelindo Kediri - Ahsinil Umam (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study aims to determine the PBL Strategy at PT Annisa Ahmada Kediri in providing an understanding of the material and knowing the advantages and disadvantages of the PBL Strategy applied. This type of research is descriptive qualitative. Information is obtained from in-depth interviews, observation, and documentation. Data analysis in this study is a qualitative descriptive analysis technique based on the theory reviewed in the literature review. The results of the study concluded that: 1. PBL strategy learning begins with preparation in planning learning activities. Then, planning learning tools. In its implementation, the mentor / muthawif plays an important role and has his own learning style. 2. Most of the pilgrims can understand the principles of the validity of Umrah, Umrah pilgrims can understand and can solve problems, pilgrims can be independent, and can recognize the conditions and environmental situation in Makkah Medina. 3. Assessment of the PBL Muthawif learning model does not conduct test assessments but in continuous assessment (non-test) because the tendency is not centered on values/numbers alone. In this case, the priority is the quality of the Umrah pilgrims.